Current practice and recommendations in UK epilepsy monitoring units. Report of a national survey and workshop. (August 2017) - Hamandi, Khalid; Beniczky, Sandor; Diehl, Beate; Kandler, Rosalind H.; Pressler, Ronit M.; Sen, Arjune; Solomon, Juliet; Walker, Matthew C.; Bagary, Manny; ,
Highlights: Current Practice and Recommendations in the UK for Epilepsy Monitoring Units. Report of a survey and one day workshop. Emphasis on seeking consensus and best practice. Abstract: Purpose: Inpatient video-EEG monitoring (VEM) is an important investigation in patients with seizures or blackouts, and in the pre-surgical workup of patients with epilepsy. There has been an expansion in the number of Epilepsy Monitoring Units (EMU) in the UK offering VEM with a necessary increase in attention on quality and safety. Previous surveys have shown variation across centres on issues including consent and patient monitoring. Method: In an effort to bring together healthcare professionals in the UK managing patients on EMU, we conducted an online survey of current VEM practice and held a one-day workshop convened under the auspices of the British Chapter of the ILAE. The survey and workshop aimed to cover all aspects of VEM, including pre-admission, consent procedures, patient safety, drug reduction and reinstatement, seizure management, staffing levels, ictal testing and good data recording practice. Results: This paper reports on the findings of the survey, the workshop presentations and workshop discussions. 32 centres took part in the survey and there were representatives from 22 centres at the workshop. There was variation in protocols, procedures and consent processes between units, and levels of observation of monitored patients. Nevertheless, the workshop discussion found broad areas of agreement on points. Conclusion: A survey and workshop of UK epilepsy monitoring units found that some variability in practice is inevitable due to different local arrangements and patient groups under investigation. However, there were areas of clear consensus particularly in relation to consent and patient safety that can be applied to most units and form a basis for setting minimum standards.